Effective treatment of SARS-CoV-2-infected rhesus macaques by attenuating inflammation (2020)
The COVID-19 pandemic caused by the SARS-CoV-2 virus has caused a significant public health crisis worldwide. Recent studies show that excessive inflammatory response is critical for SARSCoV-2 pathogenesis and COVID-19 severity,1 which can lead to acute lung injury (ALI) and acute respiratory distress syndrome (ARDS).2 One major factor for acute inflammation in SARS-CoV-2 infection is the inflammatory macrophages, which has been considered important for the production of large amounts of proinflammatory cytokines.3 Autopsy identified an intense infiltration of macrophages in the lung tissues of fatal COVID-19 patients.4 Furthermore, single-cell RNA sequencing (scRNA-seq) showed a higher proportion of macrophages presenting in bronchoalveolar lavage fluid (BALF) of severe COVID-19 patients.5 Consistent with studies of SARS-CoV-2, infiltration and accumulation of macrophages in the lung were also found in other coronavirus diseases.6 Depletion of macrophages protected mice from lethal SARS-CoV infection, highlighting the important roles of macrophages in coronavirus-induced symptoms.7 Therefore, targeting macrophages to regulate hyperinflammation in SARSCoV-2 infection could be an effective strategy to treat COVID-19 patients.